The E3 Ubiquitin Ligase UBE3C Enhances Proteasome Processivity by Ubiquitinating Partially Proteolyzed Substrates - Chu, Bernard W.; Kovary, Kyle M.; Guillaume, Johan; Chen, Ling-chun; Teruel, Mary N.; Wandless, Thomas J. (The Journal of biological chemistry, 2013)
To maintain protein homeostasis, cells must balance protein synthesis with protein degradation. Accumulation of misfolded or partially degraded proteins can lead to the formation of pathological protein aggregates. Here we report the use of destabilizing domains, proteins whose folding state can be reversibly tuned using a high affinity ligand, as model substrates to interrogate cellular protein quality control mechanisms in mammalian cells using a forward genetic screen. Upon knockdown of UBE3C, an E3 ubiquitin ligase, a reporter protein consisting of a destabilizing domain fused to GFP is degraded more slowly and incompletely by the proteasome. Partial proteolysis is also observed when UBE3C is present but cannot ubiquitinate substrates because its active site has been mutated, it is unable to bind to the proteasome, or the substrate lacks lysine residues. UBE3C knockdown also results in less substrate polyubiquitination. Finally, knockdown renders cells more susceptible to the Hsp90 inhibitor 17-AAG, suggesting that UBE3C protects against the harmful accumulation of protein fragments arising from incompletely degraded proteasome substrates. Background: An RNAi screen identified UBE3C as a key player in degradation of a model unfolded protein. Results: UBE3C knockdown results in incomplete degradation of relatively stable substrates. Conclusion: UBE3C enhances proteasome processivity to prevent the accumulation of potentially harmful protein fragments. Significance: This advances our understanding of proteasome processivity and the consequences of defects therein.